Adopsi E-Commerce Usaha Mikro Kecil Menengah (UMKM) Makanan dan Minuman di Kabupaten Lamongan Pasca Pandemi COVID-19 - Indira Shofia Maulida; Sani Rusminah (ITB AAS INDONESIA, 2023)
In the COVID-19 pandemic situation, there are 37,000 MSMEs that have gave a statement that they suffered a loss, estimated at approx. 56% of MSMEs experienced a decline in sales, around 22% reported regarding problems in the financing aspect, as much as 15% reported problems related to the distribution of goods, and as many as 4% experienced difficulties obtaining raw materials using E-commerce can accelerate the performance of MSMEs because it can minimize costs for marketing the goods or services to be sold. The aim of this research is to find out the factors that influence e-commerce adoption, namely the external environment, perceived convenience, technology readiness, attitudes towards e-commerce adoption and behavioral intentions in food and beverage MSMEs after the COVID-19 pandemic in Lamongan Regency.This research method uses quantitative data by distributing questionnaires to respondents. The sampling technique in this study was to use a simple random sampling method for MSME Food and Beverage actors. Data analysis uses index transformation analysis tools and statistical T test analysis. The results of the transformation analysis of the perceived usefulness variable index have a good percentage of 66.33%. This means that the perception of usability has a strong influence on the adoption of E-Commerce by food and beverage MSME actors in Lamongan Regency. Then based on the results of the analysis of multiple linear regression analysis on the t test, the organizational readiness variable for E-Commerce adoption has an effect of t count 3,906 > t table 1,985. This means that having organizational readiness for food and beverage MSME actors will have a positive impact on the adoption of E-Commerce in Lamongan Regency Keyword : E-Commerce Adoption, Food and Baverage, Micro Small Medium and Entreprises